HUBUNGAN POLA ASUH ORANG TUA DENGAN KEBIASAAN MEROKOK PADA REMAJA DI SMAN 1 POLANHARJO - Dinar Ariasti; Budi Kristanto; Ellen Morssy Tri Maharani (KOSALA : Jurnal Ilmu Kesehatan, 2014)
Abstract The background of this research is that the factors that influence adolescent smoking habits of parents are parenting , from the early observations researchers in October 2013 from 10 adolescents in SMAN 1 Polanharjo , 8 of them have the habit of smoking . Things that trigger their parents who smoke are smokers and who do not forbid parents to know that they smoke. The purpose of this study was to determine the relationship of parenting parents to smoking in adolescents in SMAN 1 Polanharjo. Subjects were male students of class XII at SMAN 1 Polanharjo IPS that about 40 people . After viewing the table Krecji , samples taken 36 people . The sampling technique used was simple random sampling. The method of data collection was obtained by distributing a questionnaire containing 27 statements to determine parenting parents and three statements to find out the habit of smoking in adolescents . The data collected is then analyzed with the chi square test with p=0.05. The results of the study are ( 1 ) found 1 person with parenting authotarian have the habit of smoking ( 2 ) 6 people with authoritative parenting does not have the habit of smoking , and ( 3 ) 29 people with permissive parenting has a habit of smoking . After the chi square test , p obtained for 0000 so that the value of p < 0.05, which means that Ho is rejected and Ha accepted. Research conclusion is there is a relationship between parenting parents to smoking in adolescents in SMAN 1 Polanharjo . Keywords: Parent Parenting, Smoking Habit